Advanced organic chemistry reactions and mechanisms - Miller, Bernard 1930- (Harcourt Academic Press, 2000)
Offers a guide to charting the movements of electrons and atoms during the reactions of organic molecules. This title offers instructions on writing mechanisms in organic chemistry. It contains many problem sets and answers to all problems to help students work through general principles and applications.